Analisis Teknik Dasar Futsal Pada Ekstrakurikuler di Sekolah SMPIT AL ARABI - Ahmad Fathan Kamil Kamil; Febi Kurniawan; Bambang Ismaya (Jurnal Ilmiah Wahana Pendidikan, 2021)
The problem in this research is the basic technique of futsal in extracurricular at SMPIT Al-Arabi school. This research is quantitative descriptive . The subjects of this study were all futsal extracurricular students at SMPIT Al-Arabi school. There are 20 students who take part in this futsal extracurricular. The object of this research is in the form of basic futsal techniques, namely passing, controlling, dribbling, and shooting. The setting of this research takes place in the Ganda Agung Warung Satu futsal field, Sukatani District, Bekasi Regency. The data collection technique was carried out using the Futsal Skills Test FIK Jogja. This test is used to measure the basic techniques of futsal. The data were analyzed by descriptive statistics in the form of percentages. The results of this study indicate that the level of basic futsal techniques at SMPIT Al-Arabi school as much as 1 student (5%) is declared Very Good, 4 students (20%) is declared Good, 9 students (45%) is declared Enough, 4 students (20%) declared less, and 2 students (10%) declared Less Once. The mean value of 78.56 lies in the interval 70 <X≤84, then the level of basic extracurricular futsal techniques at SMPIT Al-Arabi school is declared sufficient.